The role of adequate iodine intake during pregnancy in the prevention of violations of intelligence in children: choosing the iodine-containing drugs dosage - N A Kurmacheva (IP Berlin A.V., 2015)
The importance of accurate in prevention of iodine deficiency for planning pregnancy and pregnant women, with emphasis on its main purpose - to ensure the harmonious development of the brain of the fetus and child and prevention of cognitive impairment in offspring is discussed in this article. The importance of compliance with the modern principles of iodine prophylaxis - to ensure adequate iodine intake before conception and throughout pregnancy and breastfeeding, is demonstrated.